Off Limits: Sulfate below the Sulfate-Methane Transition - Brunner, Benjamin; Arnold, Gail L.; Røy, Hans; Müller, Inigo A.; Jørgensen, Bo B. (Frontiers in Earth Science, 2016)
One of the most intriguing recent discoveries in biogeochemistry is the ubiquity of cryptic sulfur cycling. From subglacial lakes to marine oxygen minimum zones, and in marine sediments, cryptic sulfur cycling – the simultaneous sulfate consumption and production – has been observed. Though this process does not leave an imprint in the sulfur budget of the ambient environment – thus the term cryptic – it may have a massive impact on other element cycles and fundamentally change our understanding of biogeochemical processes in the subsurface. Classically, the sulfate-methane transition (SMT) in marine sediments is considered to be the boundary that delimits sulfate reduction from methanogenesis as the predominant terminal pathway of organic matter mineralization. Two sediment cores from Aarhus Bay, Denmark reveal the constant presence of sulfate (generally 0.1 to 0.2 mM) below the SMT. The sulfur and oxygen isotope signature of this deep sulfate (34S = 18.9‰, 18O = 7.7‰) was close to the isotope signature of bottom-seawater collected from the sampling site (34S = 19.8‰, 18O = 7.3‰). In one of the cores, oxygen isotope values of sulfate at the transition from the base of the SMT to the deep sulfate pool (18O = 4.5‰ to 6.8‰) were distinctly lighter than the deep sulfate pool. Our findings are consistent with a scenario where sulfate enriched in 34S and 18O is removed at the base of the SMT and replaced with isotopically light sulfate below. Here, we explore scenarios that explain this observation, ranging from sampling artifacts, such as contamination with seawater or auto-oxidation of sulfide – to the potential of sulfate generation in a section of the sediment column where sulfate is expected to be absent which enables reductive sulfur cycling, creating the conditions under which sulfate respiration can persist in the methanic zone.